Mood Analysis of Written Utterances in Indonesia’s Covid-19 Vaccine Article in Online Newspaper - Rahma Yunita Putri; Malikatul Laila (NOTION: Journal of Linguistics, Literature, and Culture, 2022)
This research analyze the MOOD analysis in news text about Indonesia’s covid-19 vaccine in online newspapers. The purpose of this study is to explain the formula of MOOD analysis realized in grammar and to describe the speakers' mood in the application of the MOOD analysis in Indonesia's covid-19 vaccine article from online newspaper. The main focus of this research is on descriptive text articles and MOOD structure. This type of research is descriptive qualitative, the writersors present the analysis in a description based on the relevant quality on the data and the knowledge on sfl. The data were obtained by applying the theory of Gerot and Wignell (1994). The results of data analysis from six texts, in the formula there are five types of relations between the speakers and its related finite. Such as Subject + Finite (Tense), Subject + Finite (Do), Subject + Finite (Modal), Subject + Finite (Have) and Subject + Until (To be). The most commonly category that used in the online newspaper article is Finite (Tense). In the mood of the speaker, it is found that the speaker expresses certainty, possibility, uncertainty, obligation and advice. What most of the speakers said was certainty. In the analysis the writers also found the grade of modality: from high, medium, and low.